Selection and Preliminary Characterization of Temperature-Sensitive Mutants of Type 5 Adenovirus - Ensinger, Marcia J. (1972)
Eight temperature-sensitive (ts) mutants that replicate normally at 32 C but poorly, if at all, at 39.5 C have been isolated from mutagenized stocks of a wild-type strain of type 5 adenovirus. Three mutagens were employed: nitrous acid, hydroxylamine, and nitrosoguanidine. Ts mutants were isolated from mutagenized viral stocks with frequencies between 0.01 and 0.1%. All eight mutants had reversion frequencies of 10(−5) or less. Complementation experiments in doubly infected cultures at the nonpermissive temperature separated the mutants into three nonoverlapping complementation groups. Complementation yields ranged from a 2.3- to a 3,000-fold increase over the sums of the yields from the two singly infected controls. Genetic recombination was also demonstrated; approximate recombination frequencies ranged from 0.1 to 15%. Preliminary biochemical and immunological characterization of the mutants indicated that: (i) the single mutant in complementation group I did not replicate its deoxyribonucleic acid (DNA) or synthesize late proteins at the nonpermissive temperature but did inhibit host DNA synthesis to 25% of an uninfected control; (ii) the four group II mutants replicated viral DNA, shut off host DNA synthesis, synthesized penton base and fiber, but did not synthesize immunologically detectable hexon; the three mutants in complementation group III synthesized viral DNA, shut off host DNA synthesis, and made immunologically reactive capsid proteins (hexon, penton base, and fiber).